WTO agreement on safeguards and Article XIX of GATT : a detailed commentary / Fernando Piérola-Castro, Senior Counsel, Advisory Centre on WTO Law, Geneva. - Piérola Castro, Fernando (Cambridge University Press, 2022)
Drawing upon Fernando Piérola-Castro's extensive experience as a WTO practitioner, this book is a comprehensive and up-to-date overview of safeguard measures. With each chapter exploring a different provision of the agreement, it explores the relevant rules and procedures that govern safeguard investigations, the imposition of measures, the question of consultations and rebalancing and the multilateral transparency requirements of notification. Grounded in relevant case law, this book emphasises practice, logistics and risk management. Without focussing on the practice of any particular jurisdiction, it offers a general framework that can be applied to several domestic laws. It is a practical manual with the view of assisting in day-to-day problems in the handling of safeguard matters.